Mechanical Properties of Frozen Glacial Tills due to Short Periods of Thawing - Fu, Yanju; Jiang, Yao; Wang, Jiao; Liu, Ziming; Lu, Xingsheng (Frontiers in Earth Science, 2021)
Due to the warming climate, glacier retreat has left massive glacial tills in steep gullies; ice in the soil is prone to change phase resulting in the decrease of the ice strength and bonding of soil particles; collapse of thawing tills can lead to debris flows with disastrous consequences for geotechnical infrastructures. To improve our understanding of the mechanics of thawing glacial tills, we conducted unconsolidated–undrained direct shear tests on glacial tills from Tianmo gully on the southeastern Tibetan Plateau. Control specimens were not subjected to freeze–thaw action. A total of 648 specimens with three different dry densities, three initial water contents, and 18 thawing times were tested. Peak shear strength, peak stress to displacement ratio (0.857), and cohesion were the highest in frozen specimens. After a thawing time of 0.25 h, there was a marked decline in shear strength; maximum friction was 2.58, which was far below the value of cohesive strength. For thawing times of 0.25–4 h, peak strength varied little with thawing time, but cohesion decreased and internal friction angle increased with increasing thawing time. Our results indicate that thawing of the solid ice in the till during the initial phase of till thawing is the key control of peak till strength; the effect of ice on cohesion is greater during the initial phase of thawing and in loose tills. Moreover, frequent sediment recharge of gullies may be explained by the decrease of cohesion with increasing thawing time caused by short-term destruction of ice bonding.